Buddhism in Chinese history - Arthur F Wright (Stanford Univ, 1991)
The book is intended as this sort report - on work done in a relatively neglected field of study, on conclusions reached, on relationships discerned between different orders of facts or events, on problems encoutered and unsolved. Such a report has been made possible by the rapid advance of modern scholarship in the fields of Chinese and Buddhist studies; in the last forty years the mythologized accounts that passed for Chinese history have been critically analyzed, and a few periods and problems have slowly come into focus